Impacts of an e-learning system on the occurrence of work accidents in a chemical industry company. Issue 4 (25th August 2020) - Aragão, Roberto; Pereira-Guizzo, Camila; Figueiredo, Paulo S.
This study assesses the impact of a corporate training system on work accident reduction and the degree of severity of these occurrences, both before and after the implementation period of an e-learning system. An ex post facto study conducted in a unit of a multinational chemical industry company surveyed work accident records over a 14-year period. The results indicate that 689 work accidents occurred during the period. After implementing a unified e-learning system throughout the entire organisation, the total number of accidents decreased by 32%. The implications for knowledge management policies of chemical industry companies are discussed.